Dyrektywa jako podstawa prawna decyzji administracyjnej - Majczak, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
An administrative decision is the goal of the administrative procedure. In accordance with the rule of law’s principle expressed in the article 7 of The Constitution of the Republic of Poland: „The organs of public authority have to function on the basis of, and within the limits of the law”. This principle, which has been also confirmed in article 6 of Administrative Procedure Code, is inextricably connected with the necessity of the legal basis of the administrative decisions, which may be the only binding universal law provisions. It seems to be reasonable that they have the rank of enactment. Considerable impact on the legal basis for the administrative decision is as well European Union’s law. Directive is one of the European Union’s secondary law and binds, as to the result to be achieved, upon each Member State to which it is addressed. Directive requires proper implementation to national law’s system and native rules, which were a part of its transposition, become legal basis of administrative decision. Problem appears when the Member State breaches the term of the implementation or have the directive inaptly implemented. It is appropriate to assume that as long as the public authority is not disposing national law’s norm, which transposes directive and as well as it is not able to use union-friendly interpretation, public authority will not have the competence to adjudicate administrative cases
Keywords: decyzja administracyjna; harmonizacja prawa; prawo administracyjne; prawo wspólnotowe; zatrudnienie elastyczne